Prostatic arterial embolisation for men with benign prostatic hyperplasia: a Cochrane review. (13th July 2022) - Jung, Jae Hung; McCutcheon, Karen Ann; Borofsky, Michael; Young, Shamar; Golzarian, Jafar; Kim, Myung Ha; Narayan, Vikram; Dahm, Philipp
Abstract : Objectives: To assess the effects of prostatic arterial embolisation (PAE) compared to other procedures for treatment of lower urinary tract symptoms (LUTS) in men with benign prostatic hyperplasia (BPH). Methods: We included randomised controlled trials (RCTs), as well as non‐randomised studies (NRSs) enrolling men with BPH undergoing PAE vs other surgical interventions via a comprehensive search up until 8 November 2021. Two independent reviewers screened the literature, extracted data, assessed risk of bias, performed statistical analyses by using a random‐effects model, and rated the certainty of evidence (CoE) of RCTs and NRSs. Results: We found data to inform two comparisons: PAE vs transurethral resection of prostate (TURP; six RCTs and two NRSs), and PAE vs sham (one RCT). This abstract focuses on the primary outcomes in a comparison of PAE vs TURP. Short‐term follow‐up: based on RCT evidence, there may be little to no difference in urological symptom score improvement (mean difference [MD] 1.72, 95% confidence interval [CI] −0.37 to 3.81; low CoE) and quality of life (QoL; MD 0.28, 95% CI −0.28 to 0.84; low CoE) measured by International Prostatic Symptom Score. We are very uncertain about the effects of PAE on major adverse events (risk ratio [RR] 0.75, 95% CI 0.19–2.97; very low CoE). Long‐term follow‐up: based on RCT evidence, PAE may result in little to no difference in urological symptom scores (MD 2.58, 95% CI −1.54 to 6.71; low CoE) and QoL (MD 0.50, 95% CI −0.03 to 1.04; low CoE). We are very uncertain about major adverse events (RR 0.91, 95% CI 0.20–4.05; very low CoE). Conclusion: Compared to TURP, the impact on urological symptoms and QoL improvement as perceived by patients appears to be similar. This review did reveal major uncertainty as to how major adverse events compare.